IL-7 armed binary CAR T cell strategy to augment potency against solid tumors - Torres Chavez, Alejandro G.; McKenna, Mary K.; Gupta, Anmol; Daga, Neha; Vera, Juan; Leen, Ann M.; Bajgain, Pradip (Frontiers in Immunology, 2025)
IntroductionClinical studies of T cells engineered with chimeric antigen receptor (CAR) targeting CD19 in B-cell malignancies have demonstrated that relapse due to target antigen (CD19) loss or limited CAR T cell persistence is a common occurrence. The possibility of such events is greater in solid tumors, which typically display more heterogeneous antigen expression patterns and are known to directly suppress effector cell proliferation and persistence. T cell engineering strategies to overcome these barriers are being explored. However, strategies to simultaneously address both antigen heterogeneity and T cell longevity, while localizing anti-tumor effects at disease sites, remain limited. MethodsIn this study we explore a dual antigen targeting strategy by directing independent CARs against the solid tumor targets PSCA and MUC1. To enhance functional persistence in a tumor-localized manner, we expressed the transgenic IL-7 cytokine and receptor (IL-7Rα) in respective CAR products. ResultsThis binary strategy, which incorporates dual antigen targeting with transgenic cytokine support, resulted in enhanced potency, T cell expansion, and durable antitumor effects in a pancreatic tumor model compared to single antigen targeting or dual antigen targeting in absence of the transgenic cytokine support.DiscussionThe transgenic IL-7 armed binary CAR T cell approach could improve the efficacy of CAR-based therapies for solid tumors.